Investigation of Virulence Genes in Escherichia coli O157:H7 Strains Isolated from Dairy Cattle - Kalender, Hakan (Van Yüzüncü Yıl Üniversitesi, 2016)
Escherichia coli O157:H7 is one of the most important zoonotic agents worldwide. Humans can be infected by consumption of food and water contaminated with agent. Cattle areespecially considered to be the main reservoir of E. coli O157:H7.The aims of this study were to investigate the presence of E. coli O157:H7 in dairy cattle in Elazığ, and to determine virulence genes in E. coli O157:H7 isolates. A total of 300 rectal swab samples were collected from dairy cattle.E. coli O157:H7 was isolated from 11 (3.6 %) of rectal swab samples.The presence of shiga toxin (stx1 and stx2), intimin (eae) and haemolysin (hlyA) geneswas detected by polymerase chain reaction (PCR). Of the 11E. coli O157:H7 strains, 9 had stx2, hlyAand eae genes. Two strains were positive for stx1, stx2, hlyA and eae genes. The results of this study show that dairy cattle are asymptomatic carriers of E. coli O157:H7 that is pathogenic for humans.

Escherichia coli O157:H7 tüm dünyada önemli zoonotik etkenlerden biridir. Bu etken ile kontamine olmuş hayvansal gıdalar ve sular insanlar için enfeksiyon kaynağını oluşturmaktadır. Hayvan türleri içerisinde özellikle sığırlar E. coli O157:H7’nin esas taşıyıcısıdır. Bu çalışma, Elazığ’da sütçü sığırlardan E. coli O157:H7’nin izolasyonu ve izolatlarda önemli virulens genlerin varlığının araştırılması amacıyla yapılmıştır. Çalışmada, toplam 300 sütçü sığırdan rektal sıvap örneği alınmıştır. Bu örneklerin 11(% 3.6)’inden E. coli O157:H7 izole edilmiştir. İzole edilen suşlarda Şiga toksin (stx1 ve stx2), intimin (eae) ve enterohemolizin (hlyA) genlerinin varlığı Polimeraz Zincir Reaksiyonu (PZR) ile araştırılmıştır. Suşların 9’unda stx2, hlyA ve eae genleri, 2’sinde isestx1, stx2, hlyA ve eae genleri saptanmıştır. Bu çalışmanın sonuçları sütçü sığırların, insanlar için patojenik karakter taşıyan E. coli O157:H7’nin taşıyıcısı olduğunu göstermektedir.
Sütçü Sığırlardan İzole Edilen Escherichia coli O157:H7 Suşlarında Virulans Genlerinin Varlığının Araştırılması